Effect of a prebiotic galactooligosaccharide mixture (B‐GOS®) on gastrointestinal symptoms in adults selected from a general population who suffer with bloating, abdominal pain, or flatulence. Issue 11 (15th August 2018) - Vulevic, Jelena; Tzortzis, George; Juric, Aleksandra; Gibson, Glenn R.
Abstract: Background: Prebiotics exert beneficial effects upon gastrointestinal (GI) environment, but this is not always accompanied with a positive effect on GI symptoms. B‐GOS® is a prebiotic with high selectivity toward bifidobacteria and a variety of other beneficial effects in humans. Here, we investigated its effect on GI symptoms in adults who suffer with bloating, abdominal pain, and flatulence. Methods: In a double‐blind, placebo‐controlled, crossover study, 83 subjects from the general population who presented with GI symptoms during screening period and had a predicted probability of functional bowel disorder of more than 75% were randomized to receive either a placebo or the B‐GOS® treatment (2.75 g/d). Subjects were screened for the presence of GI symptoms for 1 week, they consumed the treatments for 2 weeks, and then went through a 2‐week washout period, before switching to the other treatment for the final 2 weeks. GI symptoms, bowel movements, and stool consistency were assessed in daily and weekly questionnaires. Quality of life was assessed weekly and depression and anxiety at the end of each treatment period. Results: B‐GOS® resulted in significantly ( P  < 0.001) lower scores for bloating, flatulence, and abdominal pain both from baseline and placebo at the end of first week. The effect was sustained at the end of second week. It had no effect on the number of bowel movements, consistency of stools, quality of life, or mood throughout the study. Conclusion: Results suggest that B‐GOS® could possibly be used in the management of bloating, flatulence, or abdominal pain and warrant further investigation. Abstract : Prebiotic B‐GOS was investigated in subjects selected from the general population on the presence of bloating, abdominal pain, and flatulence in a double‐blind, placebo‐controlled, crossover trial. B‐GOS was administered over a period of 2 weeks and found to result in a significant reduction in these symptoms at the end of the first and second week.